Interaction of variable diffusion coefficients with electrokinetically regulated peristalsis of Carreau-Yasuda nanofluid - Yasir Akbar; Shiping Huang; Muhammad Usman Ashraf; Kottakkaran Sooppy Nisar; Mohammad Mahtab Alam (Case Studies in Thermal Engineering, 2023)
In this analysis, the interaction of variable diffusion coefficients with electrokinetically modulated peristaltic motion of a radiative Carreau-Yasuda (CY) nanofluid is communicated. Here, ethylene glycol is used as the base fluid, and graphene nanoplatelets are considered nanoparticles. Unlike many existing studies, the thermophoretic diffusion term appearing in the equation of temperature and concentration is considered a variable term instead of manipulating their average values to obtain a more precise estimation of the conduct of the nanofluid. The Carreau-Yasuda (CY) model is considered to represent the non-Newtonian features of nanofluids. A mathematical model is developed under the effects of Joule heating, variable thermal conductivity, mixed convection, thermal radiation, electric field, Brownian motion, viscous dissipation, magnetic field, and thermophoresis assumptions. The entropy equation involving a variable diffusion coefficient and thermal conductivity is constructed using the second law of thermodynamics. The acquired dimensionless equations are numerically resolved with the help of built-in function. The graphical results indicate that due to Joule heating characteristics, the temperature profile increases. Manipulation of radiation and thermal conductivity parameters can improve the thermal efficiency and productivity of the system. An electroosmotic parameter causes an augmentation in the Bejan number. The nanofluid flow decreases at a higher electroosmotic velocity. The nanofluid chosen makes it possible to envisage industrial applications, for example in the field of heat extraction, without compromising mechanical performance.